Efektivitas Perkotaan Gemolong sebagai Pusat Pelayanan Permukiman di Kabupaten Sragen - Sri Murdiati Rin Permata Sari; Ana Hardiana; Rufia Andisetyana Putri (Regional Development Information Center, Universitas Sebelas Maret, 2017)
The nodal’s region is a region that is functionally dependent between the center (core) and the peripheral area (the area served). The existence of the order level in each center also affects the size of the service area served. The Sragen regency that is applying the concept of nodal region has two residential center; “urban Sragen” and “urban Gemolong”. Although urban Gemolong has become a nodal center of settlements for the six sub-districts which are the area of service but there are still services that are not available such as universities, museums and theaters. Apart from that, the location of Gemolong urban service area that is close to Solo, Porwodadi, and Boyolali, in which have higher order(hierarchy) would attract people in the outskirts to meet the needs of their settlement services into these cities. Therefore, this study is aim to identify the effectiveness of urban Gemolong as a settlement service center in the Sragen regency. There are two objective of this research; (1) First to identify the condition of urban service of Gemolong as settlement service center in Sragen regency in terms of effectiveness variable of settlement service center and, (2) secondly analyze the effectiveness of urban Gemolong as settlement service center in Sragen regency. The research approach used is deductive, with the quantitative research type using scoring analysis. Survey conducted for this research is the primary survey in the form of observation, and secondary survey in the form of data review. From the result, the effectiveness Gemolong urban which has three variables there is only one variable is suitable (service purpose), while service efficiency and affordability are not suitable. The effectiveness of the urban Gemolong as settlement service center in Sragen regency is approaching into effectiveness, which means it has not been effective, so it needs to be improved, especially for the availability and scope of services.